ANALISIS SISTEM PENGENDALIAN INTERNAL PENGGAJIAN KARYAWAN KANTOR AKUNTAN PUBLIK GRANT THORNTON INDONESIA - Saragih, Poetry Nathasya; Firmanto, Yuki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine and analyze the implementation of the payroll internal control system of Grant Thornton Indonesia Public Accounting Firm based on COSO (Committee of Sponsoring Organizations of the Treadway Commission). This study employs a descriptive qualitative method, and the data are collected from interviews, observation, and documentation. The results of the research analysis exhibit that the internal control system for such components as risk assessment, control activities, and information and communication has been effectively implemented, yet this is not the case for such components as the control environment and monitoring activities